Explaining Causes Of Inequity In Public Health : A Narrative Review: Inequity In Public Health - Afrona Elisabeth Lelan Takaeb (STIKes Mandala Waluya Kendari, 2022)
Objectives: This paper attempts to explain the term inequity in public health based on The Rainbow Model introduced by Dahlgreen & Whitehead (1991) and The Social determinant of Health (SDH) framework of the Commision of Social Determinants of Health). Methods: The author applied a narrative review and examined 29 relevant English literatures and found two themes. Results: First, Explanation of The Rainbow Model’ introduced by Dahlgreen & Whitehead (1991) and The SDH framework of the Commision of Social Determinants of Health. Second, the perspective of traditional public health emphasizes the proximal determinants while New Public health emphasis on intermediate determinants and distal determinants. Conclusions: Therefore, as a public health professional need to consider about proximal, intermediate and distal determinant of public health issue.